PENGARUH FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD - Puspitadewi, Esterine; Sormin, Partogian (Jurnal Akuntansi, 2018)
This study aimed to examine the effect of fraud diamond which is consists of four elements to the financial statement fraud proxied with earnings management. This study examines the pressure variables by the proxy financial target (ROA), opportunity variables by proxy ineffective monitoring (KOIN), rationalization variables by proxy total asset accruals (TATA), and capability variables by proxy changes of director (PESI). The data of the research from annual reports of manufacturing company listed on the Stock Exchange during the period 2014 â 2016. This study uses purposive sampling to select a representative sampling and the collected data analysis using multiple linear regression analysis. The results showed that the variable rationalization as measured by total asset accruals significant to financial statement fraud. While, the variable of opportunity, pressure, and capability have no effect on financial statement fraud.